The effectiveness of the implementation of QE/5S towards quality environment at workplace / Norhaslina Jumadi ... [et al.] - Norhaslina, Jumadi; Nurul Sahida, Fauzi; Lizawati, Abdullah; Wan Nur Syazwani, Wan Mohammad; Johana, Yusof (2015)
Since many organizations attempt to become the best in their service, a good management system is required and therefore, the implementation of 5S is highly recommended. 5S is known as the 5 pillars which refer to sort, set in order, shine, standardize, and sustain (Hirano, 1995). This system is a good starting point for all improvement effort and maintaining work efficiency by the staff. The application of 5S at workplace will also help in improving safety, work efficiency, productivity and a sense of ownership. However, the implementation of 5S demands a huge commitment from the top management and participation by everyone in the organization is required. UiTM (Perak) is an educational institution with almost 200 administration staff in the administration building. Since 2012, UiTM Perak has gained recognition and 5S certification from Malaysia Productivity Corporation (MPC) for the commitment of QE/5S practice at workplace. This paper attempt to discover the significance 5S implementation in a workplace and to identify the impact of the elements in 5S towards quality environment among UiTM (Perak) administration staff. A structured questionnaire was distributed randomly among UiTM staff. Data from the questionnaire was analysed using the SPSS. While for secondary data, multiple case study and literature review from various organizations were analysed qualitatively to see the gap and the best practice in sustaining the implementation of QE/5S. This research is hoped to contribute to the knowledge of the importance of QE/5S implementation and would strongly support the objectives of organization to achieve continuous improvement and quality environment in workplace.